Impact of FDG-PET on therapy management and outcome of differentiated thyroid carcinoma patients with elevated thyroglobulin despite negative iodine scintigraphy - Schleupner, Marie Carolin; Riemann, Burkhard; Schäfers, Michael; Backhaus, Philipp; Vrachimis, Alexis (Nuklearmedizin - NuclearMedicine, 2020)
Aim The objective of this study was to assess the impact of implementing FDG-PET imaging in treatment algorithms for differentiated thyroid cancer with suspected recurrence. Primary end points were overall, event-free and disease-specific survival. Secondary end points were therapies, disease control and the sensitivity and specificity of PET imaging.Methods 194 patients with DTC treated at our center from 1996 to 2014 following thyroidectomy and routine 131I ablation with no remaining 131I uptake in whole-body scans but persisting or rising thyroglobulin values were enrolled in this retrospective analysis. Of these, 149 (76.8 %) received an 18F-FDG scan (PET group) whereas the remaining 45 patients (23.2 %) did not (non-PET group). Survival, disease-specific characteristics at inclusion, disease control and therapies were compared.Results Patients of the PET group generally showed characteristics associated with higher disease activity from inclusion onwards. This did not translate to statistically significant differences in survival. If PET imaging was performed following inclusion, patients received significantly less radioiodine treatments during the first nine months after inclusion (63.1 % of the PET-group vs 82.2 % of the non-PET group). Simultaneously, patients tended to receive more surgeries following PET imaging (27.5 % PET-group vs 13.3 % non-PET group). No significant differences regarding disease control were observed.Conclusion The early use of FDG-PET imaging in cases of suspected recurrence or existence of dedifferentiated DTC can lead to changes in therapy management, specifically identifying patients unlikely to benefit from additional radioiodine therapy who would instead qualify for surgical therapy methods.
Keywords: DTC; thyroid cancer; therapy management; survival; FDG-PET; FDG-PET/CT